2020
DOI: 10.3390/ijms21176231
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone (DHT) Enhances Wound Healing of Major Burn Injury by Accelerating Resolution of Inflammation in Mice

Abstract: Androgens have been known to inhibit cutaneous wound healing in men and male mice. However, in children with major burn injuries, a synthetic androgen was reported clinically to improve wound healing. The aim of this study is to investigate the role of dihydrotestosterone (DHT) as a new therapeutic approach in treating major burn injury. In the present study, mice received systemic androgen treatment post major burn injury. Wound healing rate and body weight were monitored over 21 days. The serum level of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Both DHT and its precursor cholesterol have pro-inflammatory effect. 41 , 42 Therefore, our results suggest that, as the overall inflammation is suppressed in patients susceptible to HFS, patients with a high risk of developing grade 2 or even more severe HFS may benefit from reducing the everyday milk consumption below 95 ml.…”
Section: Discussionmentioning
confidence: 74%
“…Both DHT and its precursor cholesterol have pro-inflammatory effect. 41 , 42 Therefore, our results suggest that, as the overall inflammation is suppressed in patients susceptible to HFS, patients with a high risk of developing grade 2 or even more severe HFS may benefit from reducing the everyday milk consumption below 95 ml.…”
Section: Discussionmentioning
confidence: 74%
“…8,9 However, in contrast, the more potent, pure non-aromatizable androgen dihydrotestosterone (DHT) when administered systemically improved burn wound healing with earlier cell proliferation and collagen deposition. 10 These novel findings point to a previously unrecognized, paradoxical, and context-dependent role of androgens in wound healing that differs between burn and cutaneous injuries. The paradoxical, beneficial effects of systemic pure androgen administration on local wound healing raise the question of whether androgen receptor (AR)-mediated androgen actions may have an overlooked positive effect in local cutaneous healing of burn injury.…”
Section: Introductionmentioning
confidence: 93%
“…Rodent models have established that aromatize androgens like testosterone inhibit and prolong cutaneous wound healing in male mice, 4–7 an effect reversed by treatment with topical flutamide, an androgen antagonist 8,9 . However, in contrast, the more potent, pure non‐aromatizable androgen dihydrotestosterone (DHT) when administered systemically improved burn wound healing with earlier cell proliferation and collagen deposition 10 …”
Section: Introductionmentioning
confidence: 99%
“…Aside from a few studies showing the effect of DHT treatment on increasing mouse skeletal muscle size and strength, research on the application of DHT in burn injury wound healing are limited [ 90 , 91 ]. In our recent study, the effect of DHT treatment in major burn injury healing was examined in a burn injury mouse model [ 92 , 93 ]. Our data showed that DHT has a positive impact on both local wound healing and metabolic catabolic responses, which differs from results reported after cutaneous injury.…”
Section: Reviewmentioning
confidence: 99%
“…The increase in monocyte chemoattractant protein-1 (MCP-1) level at the wound area and systemically recruits more monocytes to the blood circulation and the wound site. These monocytes were found to differentiate to macrophages, which are involved in removing bacteria, preventing infection and contributing to collagen disposition once the inflammation is resolved [ 93 ] ( Figure 5 ). Therefore, as a safer, non-hepatoxic androgen, DHT was approved for the first time to induce acceleration of the inflammatory turnover both locally and systemically as the key in promoting major burn injury wound healing without any adverse effects.…”
Section: Reviewmentioning
confidence: 99%